A Novel Subcluster of Closely Related Bacillus Phages with Distinct Tail Fiber/Lysin Gene Combinations - Rachel E. Loney; Véronique A. Delesalle; Brianne E. Chaudry; Megan Czerpak; Alexandra A. Guffey; Leo Goubet-McCall; Michael McCarty; Madison S. Strine; Natalie T. Tanke; Albert C. Vill; Greg P. Krukonis (Viruses, 2023)
Bacteriophages (phages) are the most numerous entities on Earth, but we have only scratched the surface of describing phage diversity. We isolated seven Bacillus subtilis phages from desert soil in the southwest United States and then sequenced and characterized their genomes. Comparative analyses revealed high nucleotide and amino acid similarity between these seven phages, which constitute a novel subcluster. Interestingly, the tail fiber and lysin genes of these phages seem to come from different origins and carry out slightly different functions. These genes were likely acquired by this subcluster of phages via horizontal gene transfer. In conjunction with host range assays, our data suggest that these phages are adapting to hosts with different cell walls.